The Influence of Islamic Leadership and Islamic Work Ethics on the Islamic Performance of Employees at BPRS Lantabur Tebuireng: The Influence of Islamic Leadership and Islamic Work Ethics on the Islamic Performance of Employees - Prasetyo, Erwin Niko; Fahrullah, A'rasy (Universitas Negeri Surabaya, 2024)
The Islamic work ethic is an obligation for banks that conduct business based on Sharia principles. This research aims to determine the influence of Islamic Leadership and Islamic Work Ethics on the Islamic Performance of Employees at BPRS Lantabur Tebuireng. This research uses a quantitative approach with multiple linear regression analysis techniques. The data used is primary data through questionnaires distributed to respondents. The sample for this research was 40 employees of BPRS Lantabur Tebuireng. The results of this research indicate that Islamic work ethics partially have an influence on employee Islamic performance. Meanwhile, Islamic leadership partially has no influence on employee Islamic performance. The results of testing the coefficient of determination show that Islamic leadership and Islamic work ethics have a simultaneous influence with a percentage of 90.1% on employee Islamic performance. This research will later be able to provide insight to institutions as well as leaders and employees to apply these aspects in the world of work